The mediating role of competitive advantage in linking creativity and innovation culture to MSMEs’ business performance in Malang City: A mixed-method study - Muhammad Hidayat; Andi Ririn Oktaviani; Hardiyanty Askar; Murtianingsih Murtianingsih; Lussia Mariesti Andriany; Widya Dewi Anjaningrum (EduLite: Journal of English Education, Literature and Culture, 2026)
Micro, Small, and Medium Enterprises (MSMEs) operate in increasingly competitive environments that require sustained creativity and innovation to achieve superior performance. This study examined the mediating role of competitive advantage in the relationship between creativity, innovation culture, and business performance of MSMEs in Malang City. A mixed-method explanatory design was employed to provide both contextual depth and empirical validation. The qualitative phase involved semi-structured interviews with key stakeholders, including government representatives, MSME community leaders, and business owners, to explore ecosystem-based innovation dynamics. The quantitative phase collected survey data from 120 MSME actors selected through purposive sampling, using structured questionnaires adapted from validated measurement scales. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrated that creativity and innovation culture did not directly influence business performance; however, both variables significantly affected performance indirectly through competitive advantage. These findings indicate a full mediation effect, suggesting that internal creative and innovative capacities translate into superior performance only when transformed into strategic competitive positioning. The study extends the Resource-Based View and Schumpeterian innovation perspective by empirically validating the mediating mechanism within a local MSME ecosystem context. Practically, the results highlight the importance of strengthening innovation culture and strategic differentiation to enhance MSME competitiveness.